Case Report: Sudden very late-onset near fatal PD1 inhibitor-associated myocarditis with out-of-hospital cardiac arrest after >2.5 years of pembrolizumab treatment - Richard I. Lewis; Katharina Seuthe; Simon Lennartz; Jan-Phillip Weber; Nicole Kreuzberg; Karin Klingel; Paul J. Bröckelmann (Frontiers in Cardiovascular Medicine, 2024)
IntroductionImmune checkpoint inhibitors have advanced the outcomes of many different types of cancer. A rare but extraordinarily severe complication of these agents resembles immune checkpoint inhibitor-related myocarditis, which typically occurs within the first few weeks after treatment initiation with a mortality of 25%–50%.Case reportA 57-year-old woman had uneventfully received pembrolizumab for metastatic non-small cell lung cancer for over 2.5 years and was admitted after an out-of-hospital cardiac arrest due to ventricular fibrillation. After successful cardiopulmonary resuscitation, the initial diagnostic work-up showed elevated cardiac enzymes and a limited left-ventricular ejection fraction, while coronary angiography did not show relevant stenosis. Despite cardiac MRI being unsuggestive of myocarditis, myocardial biopsies were obtained and histologically confirmed anti-PD-1 antibody-associated myocarditis. After the initiation of prednisone at 1 mg/kg body weight, the patient gradually recovered and was discharged three weeks later with markedly improved cardiac function.ConclusionThis case resembles the first description of a very late onset irMyocarditis, occurring over 2.5 years after the start of treatment. It demonstrates the importance of contemplating that severe immune-related toxicities with a sudden onset clinical presentation may occur even after long uneventful periods of anti-PD-1 immune checkpoint inhibitor treatment. Furthermore, it underlines the critical importance of myocardial biopsies in this setting, especially when cardiac MRI remains inconclusive. Moreover, it demonstrates the necessity and benefits of early immunosuppressive treatment if immune-related myocarditis is considered a differential diagnosis.